Hitler’s Religion: The Twisted Beliefs that Drove the Third ReichRichard Weikart - Diephouse, David J. (Holocaust and genocide studies, 2018)
For more than a decade Richard Weikart has been making a case that Nazi ideology represents social Darwinism with a political face. His detailed analysis of social Darwinist thought in Germany, published in 2004, bears the telling title From Darwin to Hitler. A subsequent study, Hitler’s Ethic (2009), portrays the Führer’s social imaginary as the extension of a moral code. That code elevated promotion of the German Volk to the status of a categorical imperative, a dictate of evolutionary necessity in a world marked by ineluctable struggles between superior and inferior races for resources, living space, and cultural dominance. This argument provides an obvious backdrop to Weikart’s new book, which seeks to define the content of Adolf Hitler’s religious outlook.